Coverage of recent criticisms of Milgram's obedience experiments in introductory social psychology textbooks. (October 2015) - Griggs, Richard A.; Whitehead, George I.
This article has two purposes: (a) to broaden awareness of recent criticisms of Milgram's obedience experiments by providing a relatively inclusive review of them interlaced within a discussion of Gina Perry's main substantive criticisms and (b) to report the findings of our coverage analysis for recent criticisms in current introductory social psychology textbooks. Past coverage analyses have found a "Milgram-friendly" trend (little or no discussion or even acknowledgment of the large body of criticism published from 1964 onward) that evolved in textbooks from the 1960s to the 1990s and has become more pronounced since that time period. Our findings on coverage of recent criticisms were consistent with those of past text analyses. None of the recent criticisms were covered, even in the social psychology textbooks dated 2015. We discuss a possible explanation for these findings that involves a proposed knowledge-conserving function of social psychology textbooks.